The power of health economics and outcomes research (HEOR) in making decisions that matter - Oscar Herrera Restrepo (Magna Scientia UCEVA, 2021)
Deciding on approving and granting market access to new medical technologies such as pharmaceutical products, vaccines, or medical devices is a multifactorial research problem. Balancing out clinical performance, epidemiological implications, burden of disease, economic value, and patient preferences, among other factors, is in itself a challenging endeavor. However, this should be a mandatory requirement when making approval and market access decisions that might affect millions of people in a specific country setting. The aim of this reflection research article is twofold; first, it provides context on the important role that health economics and outcomes research (HEOR) plays in informing decision making for market access and reimbursement of new medical technologies. Second, it outlines the power of HEOR studies in guiding discussions when assessing the value of new medical technologies. Overall, this article aims at highlighting key HEOR considerations for healthcare professionals, students, and institutions interested in building analytical capabilities around this exciting and uninterruptedly growing field of knowledge.